Increased El Niño–Southern Oscillation sensitivity of tree growth on the southern Tibetan Plateau since the 1970s - Cheng, Xuehan; Lyu, Lixin; Büntgen, Ulf; Cherubini, Paolo; Qiu, Hongyan; Zhang, Qi‐Bin (International journal of climatology, 2019)
El Niño–Southern Oscillation (ENSO) affects various components of the Earth's climate systems but its role on the Tibetan Plateau remains poorly understood. Hydroclimatic changes in Asia's water tower can have substantial effects on the functioning and productivity of agricultural and natural ecosystems, and thus the wellbeing of many millions of people. Here, we use well‐replicated ring‐width chronologies from 10 juniper sites on the southern Tibetan Plateau to associate variations in tree growth with ENSO events between 1645 and 2001 CE. An empirical orthogonal function (EOF) was applied to emphasize regional growth coherency and climate sensitivity. May–June moisture availability was found to be most important for ring‐width formation, and most growth anomalies coincided with documentary evidence of hydroclimatic extremes. The superposed epoch analysis (SEA) and the composite analysis showed an increased ENSO sensitivity in tree growth on the southern Tibetan Plateau since the 1970s, possibly due to global warming, calls for integration of large‐scale ocean–atmosphere climate feedbacks into regional forest management strategies in future warming scenarios. The superposed epoch analysis (SEA) suggests a significant association between tree growth on the Tibetan Plateau and ENSO events in the past four centuries. Tree growth is sensitive to May–June moistures on the southern Tibetan Plateau, and most growth anomalies coincide with documentary evidence of hydroclimatic extremes. The increased ENSO sensitivity of tree growth since the 1970s calls for integration of large‐scale ocean–atmosphere climate feedbacks into regional forest management strategies.